Richard Clayderman Essential - Clayderman, Richard, 1953- (Music Video Distributors, 2005)
Considered by many to be the most popular pianist of all time, this handsome, Paris-born musician has charmed the masses with his brand of light, accessible classical compositions and a highly romantic demeanor. Since 1982 his concerts and records have consistently been voraciously consumed, and the Nancy Reagan-dubbed "Prince of Romance" continues to delight audiences with a dependable output of show tunes, popular classical works, and romantic standards. This collection features some of the artist's most-loved tunes, including two versions of the song that caught Europe's attention for the very first time, "Ballade Pour Adeline."